THERAPEUTIC EFFECT OF TRIDHAM AND 1,2,3,4,6-PENTA-O-GALLOYL-Î’-D-GLUCOSE ON ALTERED ENERGY METABOLISM IN MAMMARY CARCINOMA BEARING RATS - RAMAKRISHNAN, STALIN; DHARMALINGAM, KARTHICK; T PANCHANATHAM, SACHIDANANDHAM; PALANIVELU, SHANTHI (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Emerging evidence indicates that cancer is primarily a metabolic disease involving disturbances in energy production, and hence, reprogramming of cellular energy metabolism is deemed to be one of the principal hallmarks of cancer. Tridham (TD) has been used by traditional practitioners of Siddha medicine against various ailments. Hence, the present study has been designed to evaluate the therapeutic effect of TD on altered energy metabolism in mammary carcinoma-bearing rats. Methods: Adult female albino rats of Sprague-Dawley strain weighing 170-190 g were used and 7,12-dimethylbenzeneanthracene (DMBA) was used for induction of mammary carcinoma and rats were divided into seven groups. Group I - control rats, Group II - DMBA-induced rats, Group III - DMBA- and TD-treated rats, Group IV - DMBA- and 1,2,3,4,6-Penta-O-galloyl-Î²-d-glucose (PGG)-treated rats, Group V - DMBA- and cyclophosphamide-treated rats, Groups VI and VII are TD and PGG control rats. Results: Significant (p<0.05) increase in the glycolytic enzymes, hexokinase, phosphoglucoisomerase and aldolase, was observed in tumor-bearing rats whereas gluconeogenic enzymes, glucose-6-phosphatase and fructose-1,6-biphosphatase, were significantly decreased. The activities of the mitochondrial Krebs cycle enzymes, isocitrate dehydrogenase, Î±-ketoglutarate dehydrogenase, succinate dehydrogenase, and malate dehydrogenase, and respiratory chain enzymes, nicotinamide dinucleotide dehydrogenase and cytochrome c oxidase, were significantly reduced in tumor tissue of the mammary carcinoma-bearing rats. These biochemical disturbances were effectively counteracted by TD and PGG which restore the activities of all these enzymes to the respective control levels. Conclusion: TD and PGG effectively ameliorated the altered glucose metabolism resulting in the regression of breast cancer. Keywords: Breast cancer, Cancer cachexia, Carbohydrate-metabolizing enzymes, Krebs cycle.